System analysis of the pedagogical and Social psychological mechanism in higher project IT education in the school - Valery V. Glushchenko (Jurnal Pendidikan Ilmu Sosial, 2023)
The aim of this study namely to improve the quality of higher project IT education in the school by increasing the effectiveness of the pedagogical and social psychological mechanism in higher project IT education; to achieve the goal objectives the following tasks are solved in the work. This research was conducted by qualitative method with science and practice approachs. The subject of the work is the methodology of system analysis of the pedagogical and social psychological mechanism in higher project IT education in the school. The object of the work is the pedagogical and social psychological mechanism in higher project IT education. The concept and structure of the pedagogical and social psychological mechanism in higher project IT education are clarified.  The elements of the pedagogical and social psychological mechanism in higher project IT education are investigated. Based on the results the possibility of using gestalt psychology is substantiated. The development of emotional intelligence among students in the framework of project education is described. The research methods are: analytical pedagogy, psychology, system analysis, system approach, social condition. The scientific novelty of the work is the methodology and results of the study of the pedagogical and psychological mechanism in higher project IT- education.